2020
DOI: 10.1142/s0218127420500807
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Analysis of Planetary Gear Transmission System Under Support Stiffness Effects

Abstract: The transverse-torsional nonlinear model of multistage gear transmission system which is comprised of a planetary gear set and two parallel gear stages is proposed with time-varying meshing stiffness, comprehensive gear errors and gear backlash. The nonlinear dynamic responses are analyzed by applying excitation frequency and support stiffness as the bifurcation parameters. The motions of the system are identified through global bifurcation diagram, largest Lyapunov exponent (LLE) and Poincaré map. The numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…They devised a formula to calculate the time-varying meshing stiffness of tooth backlash and conducted an analysis to investigate the influence of this time-varying meshing stiffness on the dynamic properties of the system; Wei et al (2013) developed a nonlinear dynamic model for a planetary gear transmission system and conducted an analysis on the impact of nonlinear elements, such as time-varying meshing stiffness and transmission error, on the system; Wang and Zhu (2020) developed a torsional nonlinear dynamic model for the transmission system of an aviation engine. They conducted an analysis using bifurcation diagrams and FFT spectrum diagrams to illustrate the presence of distinct nonlinear dynamic characteristics in the gear system; Xiang et al (2020) introduced a nonlinear model for lateral torsional analysis of a multi-stage gear transmission system. This system is composed of a planetary gear group and two parallel gear stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They devised a formula to calculate the time-varying meshing stiffness of tooth backlash and conducted an analysis to investigate the influence of this time-varying meshing stiffness on the dynamic properties of the system; Wei et al (2013) developed a nonlinear dynamic model for a planetary gear transmission system and conducted an analysis on the impact of nonlinear elements, such as time-varying meshing stiffness and transmission error, on the system; Wang and Zhu (2020) developed a torsional nonlinear dynamic model for the transmission system of an aviation engine. They conducted an analysis using bifurcation diagrams and FFT spectrum diagrams to illustrate the presence of distinct nonlinear dynamic characteristics in the gear system; Xiang et al (2020) introduced a nonlinear model for lateral torsional analysis of a multi-stage gear transmission system. This system is composed of a planetary gear group and two parallel gear stages.…”
Section: Introductionmentioning
confidence: 99%
“…(2013) developed a nonlinear dynamic model for a planetary gear transmission system and conducted an analysis on the impact of nonlinear elements, such as time-varying meshing stiffness and transmission error, on the system; Wang and Zhu (2020) developed a torsional nonlinear dynamic model for the transmission system of an aviation engine. They conducted an analysis using bifurcation diagrams and FFT spectrum diagrams to illustrate the presence of distinct nonlinear dynamic characteristics in the gear system; Xiang et al . (2020) introduced a nonlinear model for lateral torsional analysis of a multi-stage gear transmission system.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature [9][10][11] , a multi-stage planetary gear nonlinear dynamics model was developed to investigate the dynamics of the gear system from different perspectives such as damping coefficient, tooth side clearance, meshing stiffness and impact stresses, respectively. Xiang et al [12,13] analyzed the dynamic characteristics of the gear system in terms of excitation frequency, support stiffness and gap bifurcation parameters, respectively, and concluded that the support stiffness has a greater influence on the system motion characteristics and a larger gap can make the system more stable. Liu et al [14] established a nonlinear dynamics model considering thermal deformation, studied the effect of temperature on the thermal time-varying mesh stiffness, and analyzed the effect of temperature variation on the dynamic characteristics of the system by root mean square.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic responses of gear system were analyzed with the bifurcation diagram, time series, phase trajectory, Poincar´ e map, spectrum diagram, and related three-dimensional diagrams. Xiang et al 23 established a nonlinear model of a drivetrain composed of a planetary gear set and two parallel gear stages, where time-varying meshing stiffness, comprehensive gear errors, and gear backlash were taken into account. The nonlinear dynamic responses were analyzed by applying excitation frequency and support stiffness as the bifurcation parameters.…”
Section: Introductionmentioning
confidence: 99%